Evaluación del desempeño de nuevos esquemas de modulación y acceso multiple para 5g. - Carrión Morillo, Fabián Alejandro (2019)
The effective use of the electromagnetic spectrum gives us the possibility of high fidelity communication. 5G is the next generation of mobile communications and therefore several modulation and multiple access schemes have been improved to fulfill this purpose. OFDM is the base of the fourth generation of mobile communications called LTE-Advanced in its variants of modulation and multiple access OFDMA and SC-OFDM, therefore, the modulation scheme that happens must be compatible with these technologies. OFDM has fulfilled the requirements of the standard itself, but there are other technologies that are proposed to carry out a transmission of information in 5G, schemes in the filters and compatibility with multiple antenna technologies and with the use of millimeter waves. The most optional schemes at the beginning of this investigation were FBMC, UFMC, F-OFDM and OFDM that with the use of windows is called WOLA and due to the use of the cyclic prefix it is called CP-OFDM. All the schemes are based on the filters shown in the results are described in the development of the research and it is understood the spectrum efficiency, energy efficiency and delay, in this way you can use a simulation scheme and obtain a better idea that it is a modulation and multiple access scheme that is used in 5G. In the field of multiple access, orthogonal multiple access has been used so far and the technology proposed by some industries is NOMA because it presents many different characteristics and apparently better than those of OFDMA, it offers a better use of the electromagnetic spectrum, but the cost processing is greater. This behavior is also evaluated in the simulation software. Finally, this document presents the results of the graphs that are compared with the behavior of each scheme.